1995
DOI: 10.1111/j.1365-3040.1995.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of cellulase gene family members during induced avocado fruit abscission and ripening

Abstract: The expression of specific cellulase (endo‐l,4‐β‐glucanase; EC 3‐2‐1‐4) gene family members was monitored in the mesocarp and abscission zone of mature avocado fruit. Fruit abscission was induced by either girdling of the stem or treatment with 2‐chloroethyl phosphonic acid (CEPA). Gene‐specific probes that hybridized to the 3′ untranslated region of either the cel1 or the cel2 gene of avocado were used to distinguish between RNA transcripts from these two closely related genes. Only cel1 transcripts were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…An ethylene-responsive element (ERE) [19] has been defined for the basic-type PR group of genes and a trans-acting factor identified [33]. In addition to the PR genes, the avocado fruit-softening cellulase gene [8] is of obvious interest because it may be evolutionarily related to the BAC gene and appears to be expressed in the fruit abscission zone during abscission of mature avocado fruit [44]. Although of interest for comparison, none of the gene promoters examined to date are from genes shown to correlate specifically with leaf abscission.…”
Section: Introductionmentioning
confidence: 99%
“…An ethylene-responsive element (ERE) [19] has been defined for the basic-type PR group of genes and a trans-acting factor identified [33]. In addition to the PR genes, the avocado fruit-softening cellulase gene [8] is of obvious interest because it may be evolutionarily related to the BAC gene and appears to be expressed in the fruit abscission zone during abscission of mature avocado fruit [44]. Although of interest for comparison, none of the gene promoters examined to date are from genes shown to correlate specifically with leaf abscission.…”
Section: Introductionmentioning
confidence: 99%
“…cellulase, (62)(63)(64)(65) cytochrome P-450, (66,67) and polygalacturonase, PG. (68,69) AVOe3 mRNA has been identified as a ripening-related gene, (70) and 23 cDNA clones have been identified that had homologies to PG, endochitinase, a cysteine proteinase inhibitor and several stress-related proteins.…”
Section: Gene Cloning and Estsmentioning
confidence: 99%
“…Posteriormente, Tucker et al (1988) clonaron el gen responsable de la acumulación de celulasa en la ZA de judía y demostraron que el etileno inducía significativamente su expresión en la ZA, mientras que el ácido indol-acético (IAA) la reprimía. A raíz de estos primeros trabajos, se caracterizó la expresión diferencial de genes de esta familia en la ZA de otras especies como Sambucus nigra (Taylor et al, 1994), tomate (Lashbrook et al, 1994, del Campillo y Bennet, 1996Brummell et al, 1999), pimiento (Ferrarese et al, 1995), aguacate (Tonutti et al, 1995) o cítricos .…”
Section: Enzimas Hidrolíticasunclassified
“…Por tanto, esta micromatriz de cDNA únicamente cubre un 25% de las posibles CELs presentes en el genoma de los cítricos. La Figura 30 muestra el análisis filogenético de las proteínas de la familia CEL de C. clementina y de las CELs deducidas de A. thaliana (Lashbrook y Cai, 2008), aguacate (Tonutti et al, 1995), tomate (Brumell et al, 1999;del Campillo et al, 1996;Lashbrook et al, 1994), pimiento (Ferrarese et al, 1995), soja (Tucker et al, 2007), manzano (Li y Yuan, 2008), algodón (Mishra et al, 2008), melocotón (Trainotti et al, 2006) y Dendrobium (Rungruchkanont et al, 2007) relacionadas con el proceso de abscisión. El análisis filogenético de la familia CEL mostró que el gen aCL1347Contig1 (clementine0.9_008028m.g), inducido exclusivamente en la ZAC tras 24 h de tratamiento con etileno, estaba estrechamente relacionado con otras CELs inducidas durante el proceso de abscisión en aguacate (PaCEL1; Tonutti et al, 1995), tomate (SLGH9B4;Brumell et al, 1999), pimiento (CaCEL2; Ferrarese et al, 1995) y soja (GmCEL09; Tucker et al, 2007).…”
Section: Endo-β-(1→ → → →4)-glucanasas O Celulasas (Egasas O Cels; Faunclassified
See 1 more Smart Citation